Aplicação foliar e em cobertura de nitrogênio na cultura do trigo no cerrado - Sabin Benett, Cleiton Gredson; Buzetti, Salatier [UNESP]; Silva, Katiane Santiago; Minhoto Teixeira Filho, Marcelo Carvalho [UNESP]; Andreotti, Marcelo [UNESP]; Arf, Orivaldo [UNESP] (Universidade Estadual de Londrina (UEL), 2011)
The nitrogen in wheat is essential for obtaining high yields, not only the dose but also the time and the way of application are critical, reducing potential leaching and the cost of production. The objective is evaluating leaf and sidedressing nitrogen application on wheat crop in years of 2006 and 2007. A randomized blocks design in a factorial scheme 5x3x2 was used. The treatments consisted of five doses of nitrogen in the solution (0; 2.5; 5.0; 7.5 and 10%), three application times (at tillering: 30 days after plant emergency (DAE), at full flowering (50 DAE) + in the beginning of grain formation (70 DAE) and at tillering + in the beginning of grain formation), with and without sidedressing nitrogen applied at 40 DAE, using urea as source. They were evaluated: chlorophyll and nitrogen content in leaf, number of spikelets per ear, number of grains per ear, mass of grains per ear, number of grains per spikelet, mass hectolitric, mass of 100 grains and productivity of grains. The application of nitrogen topdressing in both years, influenced the yield characteristics of wheat. The times of leaf nitrogen only affected the leaf N content. The leaf nitrogen concentrations increased linearly the number of grains per spikelets, grains per spike, chlorophyll content, grain weight per ear and grain yield, and reduced mean weight per hectoliter, only in 2007.
Leaf and sidedressing nitrogen application on wheat crop in savanna
Keywords: Triticum aestivum L.; nitrogen fertilization; times of application; urea concentration